Jet grouting - Croce, Paolo (CRC Press, 2014)
Includes bibliographical references (pages 265-278) and index; 1. Introduction -- 2. Technology -- 3. Mechanisms and effects -- 4. Column properties -- 5. Jet-grouted structures -- 6. Design principles -- 7. Design examples -- 8. Controls